Use of Winery and Animal Waste as Fertilizers to Achieve Climate Neutrality in Non-Irrigated Viticulture - Litskas, Vassilis D.; Ledo, Alicia; Lawrence, Patrick; Chrysargyris, Antonios; Giannopoulos, George; Heathcote, Richard; Hastings, Astley; Tzortzakis, Nikos G.; Stavrinides, Menelaos (My University, 2022)
There is a growing interest globally in reducing the environmental impacts of farming by reusing agricultural waste and reducing agricultural greenhouse gas (GHG) emissions. In this work, the potential of Mediterranean viticulture for GHG emissions mitigation and Carbon (C) storage in biomass and soil is examined. In a field experiment, synthetic fertilizer use was reduced by 50 and 100% after applying a winery waste-based biofertilizer, and the C balance was determined at the vineyard level. The Vineyard Carbon Tool (VCT) for GHG emissions estimation in vineyards was developed by tailoring to vineyards the widely used Cool Farm Tool (CFT). Our results show that existing conventional viticulture could be easily transformed into zero-emissions by reducing nitrogen (N) fertilizers, lowering tillage frequency, using less fuel, and maintaining field margin vegetation at the farm level. Use of Life Cycle Analysis (LCA) showed that farm input reductions lead to a vineyard lifetime C storage equal to 25,124 kg CO2-eq ha−1 or 837 kg CO2-eq ha−1 year−1. This approach could be used for the design of eco-schemes related to C farming under the new Common Agricultural Policy (CAP).
Keywords: CAP; carbon farming; climate change; LCA; product quality; sustainable agriculture